2004
DOI: 10.1023/b:mcbi.0000044381.01098.03
|View full text |Cite
|
Sign up to set email alerts
|

Protein-, gene-, and cell-based therapeutic angiogenesis for the treatment of myocardial ischemia

Abstract: Therapeutic angiogenesis aims at restoring perfusion to chronically ischemic myocardial territories by using growth factors or cells, without intervening on the epicardial coronary arteries. Despite angiogenesis having received considerable scientific attention over the last decade, it has not yet been shown to provide clinical benefit and is still reserved for patients who have failed conventional therapies. Nevertheless, angiogenesis is a very potent physiologic process involved in the growth and development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 111 publications
0
12
0
Order By: Relevance
“…Previous studies have clearly demonstrated a critical role for vascular NO bioavailability in regulating angiogenic responses (31,39,44). Furthermore, our recent studies have strongly suggested that a chronic reduction in vascular NO bioavailability may represent a major contributing mechanism underlying the progressive skeletal muscle microvascular rarefaction in the metabolic syndrome (13).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies have clearly demonstrated a critical role for vascular NO bioavailability in regulating angiogenic responses (31,39,44). Furthermore, our recent studies have strongly suggested that a chronic reduction in vascular NO bioavailability may represent a major contributing mechanism underlying the progressive skeletal muscle microvascular rarefaction in the metabolic syndrome (13).…”
Section: Discussionmentioning
confidence: 88%
“…A growing number of previous studies have indicated that the imposition of a chronic exercise regimen will increase endothelial NOS (eNOS) expression and activity, with the cumulative result of increasing NO bioavailability under con-trol conditions (4,19,29,52) and in animal models of type I diabetes mellitus (37), heart failure (55), aging (44,49), and the metabolic syndrome (1). Taken together with our previous work and that from Matsunaga et al (35,36), the present study was designed to test the hypothesis that imposition of a chronic exercise regimen would increase vascular NO bioavailability in OZR and blunt peripheral microvascular rarefaction.…”
mentioning
confidence: 99%
“…The regeneration or formation of blood vessels in the adult heart may occur simultaneously by both vasculogenesis and angiogenesis [1]. Endothelial progenitor cells participate in both processes and are important for vascular repair and maintenance [2].…”
Section: Introductionmentioning
confidence: 99%
“…Our current study uniquely studied proliferation and migration of adult mature aortic endothelial cells, and endothelial outgrowth from adult mouse aortic discs to examine the angiogenic effects of netrin-1. Compared to umbilical vein or developing vessels, aorta shares the closest physiology with large adult coronary arteries where therapeutic angiogenesis is beneficial for patients with ischemic coronary artery diseases (9,10). More importantly, the signaling mechanisms underlying netrin-1 modulation of angiogenesis were identified.…”
mentioning
confidence: 99%